Compound heterozygosity for novel AURKC mutations in an infertile man with macrozoospermia. (1st June 2020) - Bai, Shun; Hu, Xuechun; Zhao, Yun; Li, Wei; Wan, Yangyang; Jin, Rentao; Wang, Yanshi; Guo, Tonghang; Tong, Xianhong; Xu, Bo
Abstract: Among causes of infertility, teratozoospermia is characterised by a percentage of morphologically abnormal spermatozoa >4%. Macrozoospermia, one form of monomorphic teratozoospermia, is observed in <1% of cases of male infertility and is described as approximately 100% large‐headed and/or multitailed spermatozoa. This study reports that an infertile man with large‐head spermatozoa presenting compound heterozygosity aurora kinase C ( AURKC ) mutations (c.382C>T, c.572C>T) by whole‐exome sequencing. Consequently, both two novel AURKC mutations had high probability of damage‐causing and conserved across species and extremely low allele frequency in the population. Flow cytometry analysis revealed a high ratio of sperm DNA fragmentation. Two intracytoplasmic sperm injection (ICSI) procedures were attempted for the patient, but all were unsuccessful. These results indicate that sequence analysis should be performed for the variants of AURKC in Chinese patients with macrozoospermia.